2015
DOI: 10.1021/acs.est.5b02143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Daytime and Nighttime New Particle Growth at the HKUST Supersite in Hong Kong

Abstract: Particles larger than 50-100 nm in diameter have been considered to be effective cloud condensation nuclei (CCN) under typical atmospheric conditions. We studied the growth of newly formed particles (NPs) in the atmosphere and the conditions for these particles to grow beyond 50 nm at a suburban coastal site in Hong Kong. Altogether, 17 new particle formation events each lasting over 1 h were observed in 17 days during 8 Mar-28 Apr and 1 Nov-30 Dec 2011. In 12 events, single-stage growth of NPs was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 62 publications
6
56
1
Order By: Relevance
“…The FMPS was downstream of a dryer and continuously measured particles number concentrations ranged from 5.6 nm to 560 nm in 32 channels in 1-s time resolution. The FMPS was used 5 because its high time resolution can allow successfully isolating the interference associated with ship-self emissions and identifying the growth of newly formed particles from the mixing of newly formed particles and pre-existing particles (Liu et al, 2014;Man et al, 2015). However, FMPS suffers from the weakness, i.e., it was reported to underestimate particle size respect to the Scanning Mobility Particle Sizer (SMPS) and HR-ToF-AMS (Lee et al 2013).…”
Section: Cruise Description and Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FMPS was downstream of a dryer and continuously measured particles number concentrations ranged from 5.6 nm to 560 nm in 32 channels in 1-s time resolution. The FMPS was used 5 because its high time resolution can allow successfully isolating the interference associated with ship-self emissions and identifying the growth of newly formed particles from the mixing of newly formed particles and pre-existing particles (Liu et al, 2014;Man et al, 2015). However, FMPS suffers from the weakness, i.e., it was reported to underestimate particle size respect to the Scanning Mobility Particle Sizer (SMPS) and HR-ToF-AMS (Lee et al 2013).…”
Section: Cruise Description and Sampling Methodsmentioning
confidence: 99%
“…The results were caused by varying growing ceilings, which was clearly shown at OUC as well, of new particles growing to the maximum 20 sizes observed during the events in three seasons. In fact, the existence of the ceiling is the common phenomenon during the NPF events occurring in various urban or coastal atmospheres, highlighted by Zhu et al (2014Zhu et al ( , 2017 and Man et al (2015).…”
Section: Particle Number Concentrations and Size Distributions In Prementioning
confidence: 99%
“…(Fig. 9a, Zhu et al, 2014;Man et al, 2015;Guo et al, 2016). Considering (1) formation rate of new particles, e.g., J = k NucOrg [H 2 SO 4 ] m [NucOrg] n (where k NucOrg is a constant, NucOrg represents organics involved in nucleation, and m and n are two integers; Zhang et al, 2012), (2) the subsequent particle growth, and (3) H 2 SO 4 vapor to be necessary for nucleation in ambient air except at the sea beach, two scenarios were analyzed.…”
Section: Relationship Between Fr and New Particle Yieldmentioning
confidence: 99%
“…The concentration of this portion was about 6E3 cm -3 , which was the minimum Aitken mode particle concentration during the shrinkage period. Recent studies suggested that evaporation of semivolatile organics may contribute to shrinkage of particles below 40-50 nm and evaporation of ammonium nitrate may contribute to shrinkage of particles larger than 40-50 nm (Man et al, 2015). Organic vapors play a significant role in promoting the growth of freshly formed particles; therefore, the new particles may contain a considerable fraction of organic compounds after growing to Aitken mode size (Smith et al, 2008).…”
Section: Particle Shrinkage Eventsmentioning
confidence: 99%